Subcritical water extraction (SWE) for valorizing fish waste into collagen: current state and future prospects - Mohd Thani, Nurfatimah; Ling, Angel Hui Zi; Azmi, Ameera Khaireena; Mohd Thani, Suryati (Elsevier B.V., 2026)
The seafood industry generates significant waste, much of which is often discarded, contributing to environmental concerns. While conventional collagen extraction methods rely heavily on chemicals and extensive processing, these approaches pose environmental challenges due to excessive wastewater production. Subcritical water extraction (SWE) has recently emerged as a sustainable alternative, offering an efficient and eco-friendly method for recovering collagen and other bioactive compounds from fish waste. This study explores the potential of SWE as a green technology, highlighting its advantages in reducing environmental impact and enhancing resource utilization. It covers the types of collagens, their sources, and various applications, followed by a detailed discussion on the principles of SWE and the factors affecting its efficiency. The review also summarizes the findings of past studies on the use of SWE for extracting collagen from different fish waste sources, highlighting the advantages over traditional extraction methods in terms of yield, quality, and environmental sustainability. Furthermore, the paper addresses the challenges and limitations associated with the widespread adoption of SWE, such as the need for further optimization of process parameters and the integration of SWE with other green technologies. This review paper aims to provide a comprehensive understanding of the current state and future potential of using SWE for valorizing fish waste into high-value collagen, thereby addressing the environmental challenges faced by the seafood industry and promoting the development of a more circular and sustainable bioeconomy.